Solid Bar Microextraction and HPLC/DAD Determination of Diuretic Drugs and its Application to Spiked Human Urine - AL-Hashimi, Nabil; Aleih, Haneen; Al-Zoubi, Nizar; Hamed, Saja (Jordan Journal of Pharmaceutical Sciences, 2018)
In this study, solid bar microextraction combined with liquid chromatography-diode array detector (HPLC-DAD) was used for the simultaneous determination of furosemide and spironolactone in spiked human urine samples. The target drugs were extracted from aqueous sample solutions into a solid extracting sorbent located inside the lumen of a polypropylene hollow fiber with two ends sealed. After ending the extraction, analytes were desorbed by immersing the solid bar microextraction device in a micro-volume of suitable organic solvent. The effects of different variables on the extraction efficiency were investigated in order to obtain high extraction efficiency. Under the optimized experimental conditions, the calibration curves were linear in the concentration range of 10 to 100 μg L-1, with very good precision (RSD ≤ 1.53%) and low limits of detection/quantitation (LODs/LOQs were 1.45/4.85 and 2.09/6.92 μg L-1 for furosemide and spironolactone, respectively). Ultimately, the applicability of the current method was assessed by the extraction and simultaneous determination of both analytes in spiked human urine samples. The solid bar microextraction method proved to be simple, sensitive and environmentally friendly. Thus, it is a good choice for the determination of trace levels of furosemide and spironolactone in human urine using the common HPLC instrument without further cleanup procedures.